Republic of Madagascar : 2017 Article IV Consultation, First Review Under the Extended Credit Facility Arrangement, and Request for Waiver of Nonobservance of Performance Criterion, Modification of Performance Criterion and Augmentation of Access-Press Release; Staff Report; Informational Annex, Debt Sustainability Analysis, and Statement by the Executive Director for Republic of Madagascar. - International Monetary Fund. African Dept. (Washington, D.C. : International Monetary Fund, 2017)
This 2017 Article IV Consultation highlights that economic developments in Madagascar were encouraging in 2016. Driven by public investment, increasing textile exports, and accelerating activity in agroindustry, economic growth reached 4.2 percent in 2016-the highest level since 2008. Reforms continued in revenue administration, and fiscal revenue exceeded targets. Inflation was contained at 7.0 percent at end-2016. The external position strengthened significantly, benefitting from a positive shock to vanilla export prices and strong growth in manufacturing exports. In spite of current challenges, the medium term outlook is favorable. Growth is projected to accelerate, driven by the investment scaling up, tourism, garments and other light manufacturing, mining, and productivity gains in agriculture.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet